Perceptions of and interactions between locals, migrants, and tourists in South Tyrol. Issue 1 (2nd January 2022) - Marcher, Anja; Kofler, Ingrid; Innerhofer, Elisa; Pechlaner, Harald
Abstract: The nexus of migration and tourism is well explored, and both phenomena possess push- and pull factors. Their influence and connections can be seen in one of the top tourist destinations in Europe, South Tyrol, a region located in Northern Italy, and one of its most important tourism hubs: Ortisei. The area is particularly interesting for researchers due to its long history of tourism and the multilingualism of the region. Our in-depth and exploratory research approach helps gain a better understanding of the complexity of the migration-tourism nexus from a local perspective. It confirms the attractiveness of the tourism sector for migrants, but also the impact of both phenomena on the region. The findings show that the presence of migrants in a destination is strongly connected to the inflow of (domestic and international) tourists and the touristic experiences offered at the local level. Therefore, tourism contributes to the generation of in-migration. The growing share of migrants working in the local tourist industry represents the most evident link between the two phenomena, supporting the tourism-led migration hypothesis. But the local perception of tourists and migrants as the 'other' and trust as a relational characteristic joins the two phenomena on a different level, as both are seen as 'non-local' groups. However, within a tourist destination, both migrants and tourists interrelate with the local community, thus shaping it. And even though the statistical categories prevail based on the length of or reason to stay, at second glance those boundaries blur, and the acceptance of 'new' populations groups living, working and visiting the destination seems to increase with their duration of stay.